Independent financial adviser : key factors for engagement in Malaysia / Wan Azrul Wan Zainal Abidin - Wan Zainal Abidin, Wan Azrul (2010)
This study aims to investigate the key factors for engagement of the Independent Financial Adviser (IFA) in Malaysia. The objective of this study is to identify the key factor for the Malaysian public to engage the service of an IFA and their preference for the delivery of service by the IFA. This is in accordance to the initiative of the Malaysian Financial Sector Master Plan (FSMP) introduced in 2001. The finding of this research is important to the Malaysian consumer and the IFA since they would be able to mutually benefit from the understanding of how each fits into the others role and position. The study was based on data obtained from questionnaire collected from 133 respondents who are working in Klang Valley. The questionnaire consist of three parts – Section A consist of IFA engagement and service preference, Section B consist of the key factors for IFA engagement and Section C which consist of the demographics of the respondents. The data was analyzed using statistical analysis which includes Factor Analysis, Descriptive Statistics and Multiple Regression. The findings show that most of the Malaysian public is not using the service of an IFA. Nevertheless, a considerable number of them are interested to engage the service of an IFA. Among the four factors investigated, the study concludes that the personal characteristic is the only significant factor for engaging the service of the IFA to the Malaysian. This study also discusses the implications, recommendations for the IFA as well as directions for future research.